Neoadjuvant Bevacizumab Plus Docetaxel/Cisplatin/Capecitabine Chemotherapy in Locally Advanced Gastric Cancer Patients: A Pilot Study - Yu, Deguo; Wang, Zhenfeng; He, Tingbang; Yang, Lijun (Frontiers in Surgery, 2022)
Background Bevacizumab (BEV) plus chemotherapy as a neoadjuvant regimen presents good efficacy in patients with locally advanced cancer. However, its role in patients with locally advanced gastric cancer (LAGC) is not clear. Thus, the study aimed to assess the efficacy and safety of neoadjuvant BEV plus chemotherapy in patients with LAGC. Methods Twenty resectable patients with LAGC who received BEV plus docetaxel/cisplatin/capecitabine (DCC) chemotherapy for 3 cycles with 21 days as one cycle as neoadjuvant regimen were involved. Besides, their treatment response, survival profiles, and adverse events were assessed. Results In total, two (10.0%), 9 (45.0%), 8 (40.0%), and 1 (5.0%) patients achieved complete remission, partial remission, stable disease, and progressive disease (PD) according to imaging evaluation, which resulted in 55.0% of objective response rate and 95.0% of disease control rate, respectively. Moreover, the number of patients with pathological response grades 1, 2, and 3 was 8 (40.0%), 8 (40.0%), and 3 (15.0%); while 1 (5.0%) patient did not receive surgery due to PD, thus the data of this patient was not assessable. Meanwhile, 18 (90.0%) patients achieved R0 resection. Regarding survival profile, the median disease-free survival or overall survival were both not reached. The 1-year, 2-, and 3-year disease-free survival rates were 88.8, 80.7, and 67.3%. Meanwhile, the 1-, 2-, and 3-year overall survival rates were 100.0%, 75.8%, and 75.8%, respectively. Additionally, the main adverse events were anemia (90.0%), alopecia (90.0%), leukopenia (70.0%), and anorexia (65.0%). Indeed, most adverse events were of grade 1 or 2 and were manageable. Conclusion Neoadjuvant BEV plus DCC chemotherapy presents a favorable pathological response and survival profile with acceptable safety in patients with LAGC.